2007
DOI: 10.1007/s00020-007-1544-7
|View full text |Cite
|
Sign up to set email alerts
|

Some Quadratically Hyponormal Weighted Shifts

Abstract: In the study of the gaps between subnormality and hyponormality both quadratic hyponormality and the related property positive quadratic hyponormality have been considered, especially for weighted shift operators. In particular, these have been studied for shifts with the first two weights equal and with Bergman tail or recursively generated tail. In this article, we characterize the allowed first two equal weights for quadratic hyponormality with Bergman tail, and the allowed first two equal weights for posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…If we want all the d n to be non-negative, surely there is an easy way this may occur: in [9], a weighted shift W α is defined to be positively quadratically hyponormal if c(n, n + 1) > 0 and c(n, i) ≥ 0, 0 ≤ i ≤ n, n ∈ N 0 . This class of operators has been studied in, for example, [1,6,17,20]. We specialize to a class of shifts due to Stampfli and arising in his consideration of the problem of completing an initial finite sequence of weights to yield the weight sequence for a subnormal shift [22].…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…If we want all the d n to be non-negative, surely there is an easy way this may occur: in [9], a weighted shift W α is defined to be positively quadratically hyponormal if c(n, n + 1) > 0 and c(n, i) ≥ 0, 0 ≤ i ≤ n, n ∈ N 0 . This class of operators has been studied in, for example, [1,6,17,20]. We specialize to a class of shifts due to Stampfli and arising in his consideration of the problem of completing an initial finite sequence of weights to yield the weight sequence for a subnormal shift [22].…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…Subsequently several papers have considered the problem of quadratic hyponormality of W α with first two weights equal (cf. [8], [9], [10], [14], [16], [22]). On the other hand, in [21], it was shown that if W α is cubically hyponormal with first two weights equal, then W α has flatness.…”
Section: Examplesmentioning
confidence: 99%
“…In particular, weak 2-hyponormality is referred to as quadratic hyponormality. Note that the structure of quadratically hyponormal weighted shifts has been studied at some length since 1990 (see [3,[6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these and related studies have considered backward extensions, of length 1, 2 or 3, of the subnormal shift with weight sequence ( 12]; definitions are reviewed below). Many of these [3,6,9,11] have considered flatness (in which, under some condition, equality of two or three weights forces equality of all or almost all weights), and it is understood that to avoid trivialities there is no loss of generality in assuming that the weight sequence is strictly increasing except perhaps for the zeroth and first weights. An early question posed in [4] was to describe all quadratically hyponormal weighted shifts with the first two weights equal.…”
Section: Introductionmentioning
confidence: 99%